Inactivation of Sonic Hedgehog Signaling and Polydactyly in Limbs of Hereditary Multiple Malformation, a Novel Type of Talpid Mutant - Matsubara, Yoshiyuki; Nakano, Mikiharu; Kawamura, Kazuki; Tsudzuki, Masaoki; Funahashi, Jun-Ichi; Agata, Kiyokazu; Matsuda, Yoichi; Kuroiwa, Atsushi; Suzuki, Takayuki (Frontiers in Cell and Developmental Biology, 2016)
Hereditary Multiple Malformation (HMM) is a naturally occurring, autosomal recessive, homozygous lethal mutation found in Japanese quail. Homozygote embryos (hmm-/-) show polydactyly similar to talpid2 and talpid3 mutants. Here we characterize the molecular profile of the hmm-/- limb bud and identify the cellular mechanisms that cause its polydactyly. The hmm-/- limb bud shows a severe lack of sonic hedgehog (SHH) signaling, and the autopod has 4 to 11 unidentifiable digits with syn-, poly-, and brachydactyly. The Zone of Polarizing Activity (ZPA) of the hmm-/- limb bud does not show polarizing activity regardless of the presence of SHH protein, indicating that either the secretion pathway of SHH is defective or the SHH protein is dysfunctional. Furthermore, mesenchymal cells in the hmm-/- limb bud do not respond to ZPA transplanted from the normal limb bud, suggesting that signal transduction downstream of SHH is also defective. Since primary cilia are present in the hmm-/- limb bud, the causal gene must be different from talpid2 and talpid3. In the hmm-/- limb bud, a high amount of GLI3A protein is expressed and GLI3 protein is localized to the nucleus. Our results suggest that the regulatory mechanism of GLI3 is disorganized in the hmm-/- limb bud.